MODERN TRENDS OF DEVELOPMENT OF BREEDING AND SEED PROJ DUCTION OF COLE CROPS (RECAPITULATION OF THE INTERNATIONAL RESEARCH AND PRACTICE CONFERENCE OF COLE CROPS, SEPTEMBER, 2013, VNIISSOK) - L. L. Bondareva (Овощи России, 2015)
On 24-25 of September, 2013, the International Research and Practice Conference of Cole Crops was held in the All-Russian Research Institute of Vegetable Breeding and Seed Production, in terms of which the meeting of the research and methodologycal commission and open field day have been conducted.